(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Type 2 diabetes mellitus is a complex heterogeneous group of metabolic conditions characterized by an increased level of blood glucose, due to impairment in insulin action and/or insulin secretion. Normally the level of HbA1c is less than 6%. HbA1c level reveals the mean glucose level over the previous 10-12 weeks. HbA1c has become a very important part of the management of patients with diabetes mellitus. In addition, the HbA1c is a better indicator of chronic glycemic levels and has a better index to determine the risk for long-term complications as well. So for the screening or diagnosing DM by using glycated hemoglobin (HbA1c) level is very important. The aim of the study was to correlate the plasma glucose level and HbA1c in diabetic patients attending in Chitwan Medical College and Teaching Hospital. MATERIALS AND METHODS: The study was a cross sectional study carried out in Department of Biochemistry in collaboration with Department of Medicine, Chitwan Medical College, Nepal. The standard screening procedures such as fasting blood sugar (FBS), post prandial blood sugar (PPBS) and HbA1c were the parameters taken into account for the research work. RESULTS: It was found that both FBS and PPBG strongly correlated significantly with HbA1c values (r = 0.79, p <0.001 and r = 0.75, p <0.001). CONCLUSIONS: The results suggest that both fasting and postprandial blood glucose significantly correlated with HbA1c. However, our data suggest that HbA1c values may be a weak parameter to identify pre-diabetes cases. HbA1c threshold of ≥ 6.8% can be considered a relatively sensitive marker for the diagnosis of diabetes in the study population.